The Implementation of English Teaching in an Inclusive Classroom Context for Students with Intellectual Disabilities - da Silva, Endrycho Putra (Journal of Educational Study, 2025)
This study explored the implementation of English learning for students with intellectual disabilities in an inclusive classroom at SD Triamerta Singaraja, focusing on the inclusive classroom 2B with 24 students, including five with intellectual disabilities. The urgent need for this study arose from challenges faced in the inclusive education setting, such as these students’ difficulty in absorbing lessons, rapid loss of interest, and behavioral issues like tantrums and mood swings, which complicated effective teaching and learning. The study centered on the role of the inclusive teacher, who supported these students during English lessons alongside the regular teacher. Employing a qualitative case study design, data were gathered through observation checklists and interviews over four weeks on Tuesdays during English classes. Findings revealed distinct teaching procedures for students with intellectual disabilities: they were taught in small groups led by the inclusive teacher to facilitate personalized guidance, which contrasted with the regular teacher’s approach for other students. Inclusive teachers applied strategies tailored to students’ specific needs, including simplifying learning stages, using the grammar translation method with tools like Google Translate, reading aloud, incorporating simple pictures on worksheets, and employing repetition and reinforcement techniques to enhance memory retention and engagement. These methods underscored the importance of flexible and empathetic teaching approaches in inclusive education. The findings implied that addressing the unique needs of students with intellectual disabilities through adaptive instructional strategies was vital for improving their English learning outcomes and fostering a more supportive inclusive classroom environment.